2011
DOI: 10.1007/s00213-011-2618-4
|View full text |Cite
|
Sign up to set email alerts
|

Cue-elicited heart rate variability and attentional bias predict alcohol relapse following treatment

Abstract: Rationale Identification of malleable neurocognitive predictors of relapse among alcohol dependent individuals is important for the optimization of health care delivery and clinical services. Objectives Given that alcohol cue-reactivity can predict relapse, we evaluated cue-elicited high frequency heart rate variability (HFHRV) and alcohol attentional bias (AB) as potential relapse risk indices. Method Alcohol dependent patients in long-term residential treatment who had participated in mindfulness-oriente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(123 citation statements)
references
References 67 publications
2
120
0
1
Order By: Relevance
“…The non-reduction of P3 amplitudes to A stimuli would therefore reflect the emergence of a bias in the processing of alcoholrelated stimuli from Time 1 to Time 2. Similar biases that facilitate the detection and selection of substance cues have been suggested to play a causal or perpetrating role in substancerelated behaviours (Garland et al, 2012; Goldstein and Volkow, Lubman et al, 2004;Robinson and Berridge, 1993;Zironi et al, 2006;). Binge drinkers also show inhibition impairments that increase with years of consumption (Lopez-Caneda et al, 2012), leading to a neurocognitive profile characterised by preferential processing of alcohol-related cues and a lack of inhibition resources, in a moderate but increasing way with the duration of drinking habits, consistent with the dual process model theories associated with chronic drinking behaviours (Stacy and Wiers, 2010).…”
Section: Discussionmentioning
confidence: 72%
“…The non-reduction of P3 amplitudes to A stimuli would therefore reflect the emergence of a bias in the processing of alcoholrelated stimuli from Time 1 to Time 2. Similar biases that facilitate the detection and selection of substance cues have been suggested to play a causal or perpetrating role in substancerelated behaviours (Garland et al, 2012; Goldstein and Volkow, Lubman et al, 2004;Robinson and Berridge, 1993;Zironi et al, 2006;). Binge drinkers also show inhibition impairments that increase with years of consumption (Lopez-Caneda et al, 2012), leading to a neurocognitive profile characterised by preferential processing of alcohol-related cues and a lack of inhibition resources, in a moderate but increasing way with the duration of drinking habits, consistent with the dual process model theories associated with chronic drinking behaviours (Stacy and Wiers, 2010).…”
Section: Discussionmentioning
confidence: 72%
“…The latter refers to the same study as the earlier paper by Waters, Shiffman, Sayette, et al (2003), but the Stroop and visual probe task data were reported in two different articles. Significantly, only one paper to date has reported an association between attentional bias measured by the visual probe task and relapse (Garland, Franken, & Howard, 2012).…”
Section: Predictive Validity: Does Attentional Bias Predict Relapse?mentioning
confidence: 99%
“…For instance, a major meta-analysis by Field, Munafò, and Franken (2009) found that attentional bias for substance-related cues was associated with self-reported craving across substances. Relatedly, biases for alcohol cues have been associated with relapse following treatment in alcohol-dependent adults (Garland, Franken, & Howard, 2012).…”
Section: Introductionmentioning
confidence: 99%